„Go With the Flow”. Madagascar Artists Facing the Challenges of the Modern Times - Złotkowska, Joanna (Interdisciplinary Studies in Musicology, 2026)
The paper examines numerous problems faced by Malagasy artists in the 21st century, their approach to the challenges of the market, largely dependent on geopolitical conditions, and finally philosophy of life, attitude towards the troubles they encounter. Referring to the interview with the internationally recognized artist Hanitrarivo Rasoanaivo, co-founder of the musical group Tarika, as well as conversations conducted with other active musicians from Madagascar having different backgrounds and financial status (carried out as part of field research in July 2024), the author outlines their situation, difficult for economic, social and political reasons. The steadfastness of the artists and the power of human creativity are shown; despite the lack of systemic support, equipment deficits, political and economic unrest, widespread piracy and many other problems, musicians do not give up, creating art and communities, building their legacy.